IF CosX=SinX=[squareroot]?2.SinX P T CosX-SinX=[squareroot]?2.SinX

Asked by chethan U | 22nd Jul, 2012, 07:03: PM

Expert Answer:

Answer : Given : cosX+ sinX = (underroot2 )*cosX 
To prove : cosX - sinX = (underroot2 )*sinX
 
we have ,
=> (cosX+sinX)2 + (cosX -sinX) = 2
=> ( (underroot 2 ) *(cosX) ) + (cosX-sinX)= 2  { using given equation}
=> 2cos2 X+ (cosX-sinX)= 2  
=> (cos- sinX)= 2 - 2cos2 X
=> (cosX - sinX)= 2 ( sin2X )    { using 1 - cos2 X = sin2A }
 
taking the square root both the sides we get ,
 
=>  cos-  sinX = (underroot2 )*sinX
            Hence Proved 

Answered by  | 22nd Jul, 2012, 08:54: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.